2008
DOI: 10.1007/s10681-008-9693-6
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen efficiency of canola genotypes varies between vegetative stage and grain maturity

Abstract: There is no information on whether N efficiency in canola at maturity can be reliably determined by screening germplasm in the vegetative stage. Twelve canola genotypes identified in preliminary screening study as having either high or low N efficiency indices were tested for consistency in N efficiency between the vegetative stage and maturity. Plants were grown in a glasshouse under low or adequate N supply and N efficiency was assessed using the following criteria: dry weight at deficient N supply, relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…To date much research on developing breeding strategies to improve NUE focuses on main crops including cereals, such as wheat and maize (e.g., Le Gouis et al 2000;Dawson et al 2011;Han et al 2015) and oilseed crops such as canola and oilseed rape (e.g., Balint and Rengel 2008;Berry et al 2010;Kessel et al 2012). NUE of leafy vegetables such as spinach (Chan-Navarrete et al 2014, lettuce (Kerbiriou et al 2014), or cabbage (Schulte auf'm Erley et al 2010) and NUE of non-leafy vegetable crops such as potato (Ospina et al 2014) receive less attention.…”
Section: Objectives Of the Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…To date much research on developing breeding strategies to improve NUE focuses on main crops including cereals, such as wheat and maize (e.g., Le Gouis et al 2000;Dawson et al 2011;Han et al 2015) and oilseed crops such as canola and oilseed rape (e.g., Balint and Rengel 2008;Berry et al 2010;Kessel et al 2012). NUE of leafy vegetables such as spinach (Chan-Navarrete et al 2014, lettuce (Kerbiriou et al 2014), or cabbage (Schulte auf'm Erley et al 2010) and NUE of non-leafy vegetable crops such as potato (Ospina et al 2014) receive less attention.…”
Section: Objectives Of the Reviewmentioning
confidence: 99%
“…Balint and Rengel (2008) concluded that screening oilseed rape for NUE for breeding purposes would require assessment at maturity, as there was little consistency in NUE ranking between vegetative stage and maturity.…”
Section: Oilseed Rapementioning
confidence: 99%
“…Rape biomass or stand density in the field is a prerequisite for optimized N application rate (Thoren and Schmidhalter 2009). Balint and Rengel (2008) reported that rape dry matter of stems, leaves, siliques and seeds were strongly influenced by genotypic differences, but only stems and seeds were affected by the treatment of N application. Mahli et al (2007) indicated that hybrid cultivars generally produced more biomass and seed yield than openpollinated cultivars, and provided greater net economic returns under both moist and relatively dry conditions.…”
Section: Apparent Recovery N Use Efficiencymentioning
confidence: 99%
“…These results highlight an efficient N remobilization from source organs during monocarpic senescence, but also reveal variations for the residual N amount in stems compared with leaves of four winter oilseed rape genotypes [ 12 ]. In addition, a genotypic and N-supply interaction for N content in stems was found for 12 genotypes of spring canola [ 22 ] and the genotype with the best N remobilization was able to better remobilize N from stems and pod walls to seeds [ 23 ]. These results suggest that stems can also be important organ for improving seed N-filling, but the role of stems in N management at the whole plant level for winter oilseed rape remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%